2014
DOI: 10.1186/s12917-014-0293-5
|View full text |Cite
|
Sign up to set email alerts
|

Parasite distribution and associated immune response during the acute phase of Toxoplasma gondiiinfection in sheep

Abstract: BackgroundIn many countries, Toxoplasma gondii (T. gondii) is a major cause of reproductive disorders and abortions in the sheep industry, and therefore responsible for important financial and economic losses. In addition, undercooked infected lamb is an important risk factor for human toxoplasmosis.In the present study, the initial phase of the infection was investigated: the parasite’s entry site, the subsequent distribution of the parasite and the host-immune response.ResultsParasite DNA was already detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
5
15
0
Order By: Relevance
“…Peripheral blood MCs (PBMCs) were isolated from heparinized blood samples with density gradient centrifugation as described (Verhelst et al, 2014). Mononuclear cells (MCs) from the duodenum, jejunum, ileum and mediastinal lymph nodes were harvested in RPMI (1640; Gibco, Merelbeke, Belgium) supplemented with 100 U/ml penicillin and 100 µg/ml streptomycin (P/S; Gibco) as described (Verhelst et al, 2011).…”
Section: In Vitro Antigen Recall Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral blood MCs (PBMCs) were isolated from heparinized blood samples with density gradient centrifugation as described (Verhelst et al, 2014). Mononuclear cells (MCs) from the duodenum, jejunum, ileum and mediastinal lymph nodes were harvested in RPMI (1640; Gibco, Merelbeke, Belgium) supplemented with 100 U/ml penicillin and 100 µg/ml streptomycin (P/S; Gibco) as described (Verhelst et al, 2011).…”
Section: In Vitro Antigen Recall Assaymentioning
confidence: 99%
“…After ingestion, the cyst wall protects the parasites from the gastric pH and ensures passage to the small intestine where they excyst upon contact with bile salts and trypsin (Dubey, 1997;Dubey et al, 1998). Upon excystation, initial bradyzoite invasion and replication takes place at the tips of the villi and subsequently results in the release of tachyzoites into the lumen to colonize neighboring villi and in the lamina propria to disseminate in the host (Dubey, 1997;Dubey et al, 1998;Coombes et al, 2013;Verhelst et al, 2014). In mice, the proximal jejunum seems to be the preferred replication site (Gregg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma gondii trophozoites replicate in the small intestinal mucosa, mucosal lymphoid tissues and draining lymph nodes. At 3 weeks post‐infection, no T. gondii DNA could be detected from the intestine . Epithelial cells may respond directly to T. gondii infection and recruit early mucosal immune responses .…”
Section: Discussionmentioning
confidence: 99%
“…41 Moreover, Sukhumavasi et al 42 suggested that IFNγ production by infection, no T. gondii DNA could be detected from the intestine. [43][44][45] Epithelial cells may respond directly to T. gondii infection and recruit early mucosal immune responses. 46 Therefore, control of the infection in early stages is most beneficial; that is why we used Giardia cyst extract on the second day post-infection with Toxoplasma suggesting that the immune response will be augmented.…”
Section: Discussionmentioning
confidence: 99%
“…Abortion is one of the main signs produced by T. gondii infection in sheep and causes economic losses in many countries due to the high prevalence of infection in this species (SILVA et al, 2013a; VAN DEN BROM et al, 2012;VERHELST et al, 2014). The main purpose of this review is to summarize the abortion outbreaks and reproductive disorders that are caused by T. gondii infection in sheep, also addressing aspects of the biology, diagnosis, prevention and control of the parasite.…”
Section: Introductionmentioning
confidence: 99%